Recent advances in adipose-derived mesenchymal stem cell-derived exosomes for regulating macrophage polarization - Dong, Zhewei; Fu, Yingli; Cai, Zhongming; Dai, Hao; He, Yucang (Frontiers in Immunology, 2025)
Adipose-derived mesenchymal stem cells (ADSCs) exhibit superior immunomodulatory properties and have broad therapeutic applications. They induce macrophage M2 polarization for anti-inflammatory responses. Exosomes derived from ADSCs (ADSC-EXOs) exhibit biological functions similar to those of ADSCs but can circumvent the limitations associated with cellular injection therapies. Potent anti-inflammatory substances contained in exosomes include the glycoprotein MFGE8, the cytokines such as prostaglandin E2, IL-6, and IGF, as well as non-coding nucleotides (miR-451a, miR-23, miR-30d-5p, let-7, lncRNA DLEU2, circRps5, Circ-Ptpn4, and mmu_ circ_0001359). The anti-inflammatory and immunomodulatory properties of these exosomes provide new perspectives for therapeutic approaches for graft inflammation, bone healing, acute lung injury, kidney stones, myocardial infarction, and diabetes-related diseases. This review summarizes the contents and functions of ADSC-EXOs, outlines their properties and the characteristics of macrophage phenotypes, and emphasizes their impact on macrophage polarization and their contribution to immune-related diseases.